Retelling Trickster in Naapi's Language - Howe, Nimachia (Book collections on Project MUSE., 2019)
"An examination of Niitsitapisinii (Blackfoot) origin stories about one of the powerful and unpredictable creators in Niitsitapii consciousness: Naapi. Through in-depth linguistic analysis, Howe reinterprets the earliest references to Naapi, offering an authentic understanding of his identity and the meanings and functions of the stories he appears"--Provided by publisher.